Anomalous high-density spin noise in a strongly interacting atomic vapor - J. Delpy; N. Fayard; F. Bretenaker; F. Goldfarb (Physical Review Research)
Spin noise spectroscopy (SNS) has become a mainstream approach to probe the dynamics of a spin ensemble in and out of equilibrium. Current models describing spin noise in interacting samples are based on an effective single-particle dynamics in a bath. Here, we report the observation of a strong interaction regime which significantly affects the spin dynamics. Performing SNS in a dense rubidium vapor, we observe anomalous distortions of the usual spin noise spectra, which we attribute to resonant dipole-dipole interaction within the ensemble. As the density of the vapor increases, we observe a dramatic broadening of the usual resonances and the emergence of an unexpected extra low-frequency noise component. We use a simple microscopic two-body numerical model to reproduce and discuss these observations. Our results suggest that the spectra cannot be described by the usual models of single-atom dynamics and arise from the evolution of interacting pairs of atoms. This work opens the way to the study of many-body spin noise or higher-order correlators in atomic vapors using SNS.